The Response of Broiler Finisher Birds Fed Graded Levels of Yam Peel Meal in Place of Maize-Based Diets - Akinmutimi, A.H.; Onen, G.E. (International Journal of Poultry Science, 2008)
Performance of broiler finisher birds fed graded levels of yam peel meal in place of maize-based diets was investigated. 120 Anak broilers with likely equal weights were randomly allocated to 4 dietary treatments. Each treatment having 3 replicates with 10 birds per replicate in a completely randomized design (CRD). Diet 1 which was maize-based served as control, while yam peel meal quantitatively replaced 5%, 10% and 15% of maize meal in diets 2, 3 and 4 respectively. Each diet was offered ad libitum to the broiler birds for 28 days. Yam peel meal consists of 89.25 dry matter, 12.17 crude protein, 9.3 ash, 6.3 crude fibre, 1.05 crude fat and 2.980kcal/g gross energy. Anti-nutritional factors like tannin (0.57), saponin (0.87), oxalate (1.19), phytate (0.89), trypsin inhibitor (0.0) are in yam peel meal. There were no significant (P<0.05) differences for the mean values of growth performance among the diets but all the same, diet 2 is most favoured numerically. There were significant (P<0.05) differences for all the parameters considered for cut parts, with the exception of wing, thigh and breast cut. Over all, it favoured diet 2 among others. For serum chemistry (total protein, urea, creatinine, alkaline phosphatase and albumin) values fall within the normal range of biochemical indices for broilers. For gross margin, diet 2 had the highest value (151.36) when compared with the control diet (138.5), diet 3 (126.80) and diet 4 (101. 47). Judging from growth performance, carcass characteristics, biochemical values and economics of the diet, diet 2 is recommended.